International Monetary Fund Annual Report 1964. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1964)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1964. The report highlights that output expanded during 1963 at a satisfactory rate in all the industrial countries. In North America, the economic upswing that began more than three years ago continued through 1963 and appeared to be accelerating in early 1964. In the United Kingdom, recovery early in 1963, following several years of limited growth, was stimulated by expansionary policies, and gained momentum during the course of the year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet